Effects of training and display content on Level 2 driving automation interface usability. (February 2020) - Mueller, Alexandra S.; Cicchino, Jessica B.; Singer, Jeremiah; Jenness, James W.
Highlights: Training improves detection of L2 notifications for lane centering but not for ACC. Information used to identify L2 activity varies with training and display content. System status recognition improves with use of appropriate display information. Training only moderately improves comprehension of system limitations. Persistent system statuses are better understood than changes that may require action. Abstract: Introduction: Level 2 driving automation features, such as adaptive cruise control (ACC) combined with lane centering, primarily communicate their operating statuses through the instrument cluster. It remains unclear how interface-specific training and display content influence the ability to understand Level 2 activity in production vehicles. Methods: Eighty participants viewed videos recorded from the driver's point of view in a variety of driving scenarios with Level 2 activity displayed in the instrument cluster of a 2017 Mercedes-Benz E-Class. Half viewed one of two instrument cluster layouts (simple or complex), and half received an orientation to the interface before the experiment. After each video, they were asked about the scenario they had just seen. We then examined what information in the displays participants used to identify Level 2 activity and the usability of the displays. Results: Training improved recognition accuracy of when lane centering was temporarily inactive and understanding of why it was inactive. Neither training nor display content affected the ability to recognize when ACC had adjusted the vehicle's speed or detected a vehicle ahead, or when ACC initially did not detect a lead vehicle and understanding of why it had not detected it. Both factors influenced which sources of information participants used to determine Level 2 activity. Recognition accuracy of system activity improved when participants used valid sources of information. Training, but not display content, improved lane centering usability, but not ACC usability. Discussion: Basic training improves detection of notifications that potentially require further driver action, but not of those that display persistent status information. Training does not result in full understanding of all system notifications or functional limitations, which reinforces the need for intuitive, salient communication about system behavior and its limitations.